2019
DOI: 10.1186/s12885-018-5249-x
|View full text |Cite
|
Sign up to set email alerts
|

oipA “on” status of Helicobacter pylori is associated with gastric cancer in North-Eastern Brazil

Abstract: BackgroundAlthough, outer membrane protein OipA of Helicobacter pylori has been associated with gastric mucosal damage and gastroduodenal diseases, studies evaluating gastric cancer patients are scarce. We investigated whether the functional oipA “on” status was associated with gastric cancer in the North-eastern Brazil, region with high prevalence of gastric cancer.MethodsWe included samples from 95 H. pylori positive subjects (23 patients with gastritis, 24 with gastric cancer, 32 first-degree relatives of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The strains expressing a functional OipA are reportedly involved in bacterial adherence to the gastric epithelial cells with mucosal damage [38] and association with host cell apoptosis [39], interleukin (IL)-8 induction [38], duodenal ulcers [104], and gastric cancer development [105,106]. A study report highlighted the oipA gene’s association with chronic gastritis development.…”
Section: Virulence Factors Associated With Colonization Of Epithelmentioning
confidence: 99%
“…The strains expressing a functional OipA are reportedly involved in bacterial adherence to the gastric epithelial cells with mucosal damage [38] and association with host cell apoptosis [39], interleukin (IL)-8 induction [38], duodenal ulcers [104], and gastric cancer development [105,106]. A study report highlighted the oipA gene’s association with chronic gastritis development.…”
Section: Virulence Factors Associated With Colonization Of Epithelmentioning
confidence: 99%
“…Three H. pylori outer membrane proteins (HomB, HopQ, and HopH (OipA)) are associated with gastric cancer [89,90]. The specific outer inflammatory protein antigen (OipA) receptor has not been identified [91].…”
Section: Helicobacter Outer Membrane Proteins and Gastric Cancermentioning
confidence: 99%
“…Many studies have suggested that the expression of OipA was positively correlated with PU, GC, and MALT in both Asian and Western strains [50][51][52]. Mahboubi et al inoculated mice with OipA vaccine and the amount of H. pylori colonized in the stomach was significantly reduced, as well as the inflammation after some time.…”
Section: Oipa (Hoph)mentioning
confidence: 99%